Preparation and characterization of cobalt- zinc catalyst SBA 15 supported for fischer-tropsch synthesis: effect on zinc loading - Muhammad Zakwan, A. Razak (2010)
The influence of promoter (Zn) on the physiochemical and catalytic properties of mesaporous silica Co/SBA-15 catalysts for the Fischer-Tropsch (FT) synthesis was investigated. SBA-15 was synthesized as support. The mesoporous silica Co-Zn/SBA-15 catalysts were prepared by incipient wetness impregnation method. Cobalt nitrate and zinc nitrate were used as sources of metal that are introduced onto catalysts with same cobalt loading (15 wt %) and different zinc loading (5 wt %, 10 wt%, 15 wt %) The characterization of catalysts was performed by using Fourier transform infrared (FTIR), scanning electron microscopy (SEM) and thermogravimetric analysis (TGA). The results for FTIR were identification of Si-O-Si functional group indicating the absortion of silica inside SBA-15 support. Beside that, the identification of metal inside SBA-15 was determined by comparing the pure SBA-15 with the incorporated metal on SBA-15. For SEM analysis the image shows that the rope like domain aggregated to wheat-like microstructure. For this research, the characterization of the catalyst by selecting Zn as promoter have quiet similar characterization with noble metal that have been already investigate.